How use two continent part and both diction civiler learn part movement earth gymnastic - Hantosh, Salam; Eassen, Israa; Tohma, Emad (Journal of Physical Education, 2008)
The definition of research Continents door begin important subject later middle sport import lea teachers exam now envelope mi dale Learn and look diction circles one in diction learn and work in use pupil behalf in of in this in part works imp or ant this diction behoove best learn tchaviourish . deter misact suggest in diction old his more found and use in learn sport and dictions found now in exam diction circle no in tersest interim on every sport canonistic and found small Fashion subject : Speak towage part and Biotin diction circle learn part move Offer subject different that meaning muse faction creel learn part move meant earth gumnastic. Offer subject : Found different that mean in muse faction circle human learn part move meant gumnastic . Found different that meaning use way part learn by chicly Haman . Found different that meaning use part learn fruition by sidle Arab. Pineapple subject : Principle Haman :pupils second in sport_minstry AL-mastusryia principle present . Principle plases playing open class sport _misery Al mastusryia Door forth: In this door offer effect decided the instruct subject offer . Door fifth In through subject construe floured placation cautious: 1- the two may both and part the learn move meant over heals 2- the way part caution learn over heats human and paver heels Arabian gymnastic . 3- the way Both certainly develop learn two movement over heels human and over heels al,Rabyia . Such construe three pouts: 1-use two way Both and part learn moment gymnastic . 2-care subbing doom use way part movement earth gymnastic en